2011
DOI: 10.1007/s12185-011-0951-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in EBV-DNA load between peripheral blood and cerebrospinal fluid in a patient with isolated CNS post-transplant lymphoproliferative disorder

Abstract: Post-transplant lymphoproliferative disorder (PTLD) is a fatal complication of allogeneic hematopoietic stem cell transplantation (HSCT) that is caused by reactivation of Epstein-Barr virus (EBV). A successful approach, monitoring EBV-DNA load in peripheral blood (PB) accompanied by preemptive rituximab therapy, has recently been reported. Here, we describe a 29-year-old woman who developed isolated central nervous system (CNS) PTLD. She received HSCT against acute myelogenous leukemia from a related human leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
1
19
1
1
Order By: Relevance
“…Serological markers, such as increasing EBV load [26,27] or chemokine (C-X-C motif) ligand 13 (CXCL13) [28] and positron emission tomography with [18F]-2-fluoro-2-desoxy-glucose [29] may facilitate discrimination between PTLD and other posttransplant complications, but these methods have a much lower specificity and sensitivity than histology and are therefore not applicable for primary diagnostics. Furthermore, serological markers are mainly analyzed in extracranial PTLD, although cerebral manifestation can be associated with no detectable EBV in the peripheral blood but EBV positivity in the liquor [30,31]. …”
Section: Pathogenesis and Origin Of Ptldmentioning
confidence: 99%
“…Serological markers, such as increasing EBV load [26,27] or chemokine (C-X-C motif) ligand 13 (CXCL13) [28] and positron emission tomography with [18F]-2-fluoro-2-desoxy-glucose [29] may facilitate discrimination between PTLD and other posttransplant complications, but these methods have a much lower specificity and sensitivity than histology and are therefore not applicable for primary diagnostics. Furthermore, serological markers are mainly analyzed in extracranial PTLD, although cerebral manifestation can be associated with no detectable EBV in the peripheral blood but EBV positivity in the liquor [30,31]. …”
Section: Pathogenesis and Origin Of Ptldmentioning
confidence: 99%
“…This discrepancy between CSF and serum has been encountered previously in cases of EBV-associated PTLD, optic neuritis, and encephalitis (3, 13-15). Potential explanations include the use of two different PCR assays for CSF and serum samples, preferential replication of the virus in the CNS, or presence of PCR inhibitor in the peripheral blood.…”
Section: Discussionmentioning
confidence: 54%
“…[8] However, for patients presenting with isolated cerebral PTLD, it is unclear whether the EBVDNA concentration in the CSF can be used as an indicator of PTLD. [3,9] In the presented case, although EBER in situ hybridization and LMP-1 staining in the brain biopsy were positive, the EBVDNA concentration indicated that the viral load in the serum and CSF was normal at the time of PTLD diagnosis and progression. We were unable to determine whether it is useful to examine the EBVDNA concentration in patients with isolated cerebral PTLD.…”
Section: Discussionmentioning
confidence: 62%
“…Till date, only 14 cases have been reported in the literature, and none occurred in lymphoma patients. [2,3] In this paper, we report the first case of a B-cell lymphoma presenting with an isolated PTLD in the CNS after HSCT.…”
Section: Introductionmentioning
confidence: 99%